PENGARUH KEMAMPUAN KERJA DAN LINGKUNGAN KERJA TERHADAP EFEKTIVITAS PELAYANAN KESEHATAN DI UNIT PELAKSANA TEKNIS DAERAH PUSKESMAS KARANGNUNGGAL KABUPATEN TASIKMALAYA - Anwar Nasihin; Basuki Rahmat; Ivan Dicksan; Beni Hartanto (CV Widina Media Utama, 2026)
This research aims to analyze the influence of employee work ability and the work environment on the effectiveness of healthcare services at the UPTD Puskesmas Karangnunggal, Tasikmalaya Regency. The primary challenges underlying this study include low interpretation of clinical protocols, interpersonal communication barriers, and inadequate information technology infrastructure. The research employs a quantitative method, involving community health center (Puskesmas) employees as respondents. Data were collected to measure the contribution of variables, both partially and simultaneously, toward achieving service effectiveness within the institution. The results indicate that employee work ability is categorized as